2017
DOI: 10.1245/s10434-017-6043-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for Women with Minimal-Volume Ductal Carcinoma In Situ Completely Excised at Core Biopsy

Abstract: Introduction Overdiagnosis and overtreatment of ductal carcinoma in situ (DCIS) are concerns, especially in women with low-volume screen-detected DCIS. We sought to evaluate outcomes in such patients. Methods Women with minimal-volume DCIS (mDCIS, defined as diagnosed with DCIS by core biopsy but no residual disease on surgical excision) treated with breast-conserving surgery from 1990–2011 were identified. Ipsilateral and contralateral breast events (IBE and CBE) were compared by competing-risk (CR) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…The incorporation of the protein biomarkers and the four DS clinicopathologic factors in the DCISionRT algorithm allowed for further risk stratification of patients with traditionally low-risk clinicopathology factors, as 50% of these patients had elevated categorical DS (Table 4). This observation is consistent with prior studies showing that some BCS-treated patients with smaller size or lower grade DCIS tumors still had substantial 10-year recurrence in the DS elevated risk group (4,28). Thus, use of categorical DS may lead to more refined risk estimates than clinicopathology alone.…”
Section: Discussionsupporting
confidence: 90%
“…The incorporation of the protein biomarkers and the four DS clinicopathologic factors in the DCISionRT algorithm allowed for further risk stratification of patients with traditionally low-risk clinicopathology factors, as 50% of these patients had elevated categorical DS (Table 4). This observation is consistent with prior studies showing that some BCS-treated patients with smaller size or lower grade DCIS tumors still had substantial 10-year recurrence in the DS elevated risk group (4,28). Thus, use of categorical DS may lead to more refined risk estimates than clinicopathology alone.…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this information has never been demonstrated before; one study demonstrated a similar rate of minimal-volume DCIS, but the association with underestimation was not investigated. 31 In our study, the minimal-volume DCIS was higher for the predicted low-risk group.…”
Section: Discussionsupporting
confidence: 43%
“…A rate of 9.3% was reported. 31 Second, of the underestimated invasive breast cancers the information on unfavourable features is of interest; the reported Her2Neu status is quite high 22,23 and the hormonal receptor statuses vary [21][22][23]25,26 .…”
mentioning
confidence: 99%
“…Among tumours larger than 20 mm, Pinder and colleagues reported that low‐/intermediate‐ and high‐grade DCIS had a lower risk of ipsilateral recurrence (DCIS or invasive) compared to very high‐grade DCIS (defined as high‐grade DCIS + >50% solid architecture + >50% ducts with comedo necrosis), although the results were not statistically significant ( P = 0.09). However, it is interesting to note that a recent study by Muhsen et al . documented 5‐ and 10‐year ipsilateral breast recurrence rates of 4.3 and 12.3% for low‐volume screen‐detected DCIS that had been completely excised at core biopsy, showing that even very small‐sized DCIS may have the potential for recurrence.…”
Section: Discussionmentioning
confidence: 99%